Multiplexed Discrimination of Single Amino Acid Residues in Polypeptides in a Single SERS Hot Spot. Issue 28 (7th May 2020) - Huang, Jian‐An; Mousavi, Mansoureh Z.; Giovannini, Giorgia; Zhao, Yingqi; Hubarevich, Aliaksandr; Soler, Miguel A.; Rocchia, Walter; Garoli, Denis; De Angelis, Francesco
Abstract: The SERS‐based detection of protein sequences with single‐residue sensitivity suffers from signal dominance of aromatic amino acid residues and backbones, impeding detection of non‐aromatic amino acid residues. Herein, we trap a gold nanoparticle in a plasmonic nanohole to generate a single SERS hot spot for single‐molecule detection of 2 similar polypeptides (vasopressin and oxytocin) and 10 distinct amino acids that constitute the 2 polypeptides. Significantly, both aromatic and non‐aromatic amino acids are detected and discriminated at the single‐molecule level either at individual amino acid molecules or within the polypeptide chains. Correlated with molecular dynamics simulations, our results suggest that the signal dominance due to large spatial occupancy of aromatic rings of the polypeptide sidechains on gold surfaces can be overcome by the high localization of the single hot spot. The superior spectral and spatial discriminative power of our approach can be applied to single‐protein analysis, fingerprinting, and sequencing. Abstract : Sequencing in a hot spot : Sequencing of single proteins by surface‐enhanced Raman spectroscopy (SERS) suffers from the signal dominance of aromatic amino acid residues and backbones, which hampers the ability to detect nonaromatic amino acid residues. A single, localized SERS hot spot in an electroplasmonic trap that allows the discrimination of aromatic and nonaromatic residues in single polypeptides is presented.